2009
DOI: 10.1038/nature08181
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage elastase kills bacteria within murine macrophages

Abstract: Macrophages are aptly positioned to function as the primary line of defence against invading pathogens in many organs, including the lung and peritoneum. Their ability to phagocytose and clear microorganisms has been well documented1 , 2. Macrophages possess several substances with which they can kill bacteria, including reactive oxygen species, nitric oxide, and antimicrobial proteins3 -9 . We proposed that macrophage-derived proteinases may contribute to the antimicrobial properties of macrophages. Macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 30 publications
1
132
2
3
Order By: Relevance
“…Recent studies have reported that MMP12 expressed in macrophage phagolysosomes has potent antimicrobial activity (12). Moreover, data presented in Fig.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 82%
See 1 more Smart Citation
“…Recent studies have reported that MMP12 expressed in macrophage phagolysosomes has potent antimicrobial activity (12). Moreover, data presented in Fig.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 82%
“…Our data suggested that the level of Mmp12 expression correlated with the level of P. murina clearance from the lungs, thus bringing into question whether MMP12 possessed the ability to directly inhibit the growth of P. murina. Indeed, a 20-amino acid sequence in the carboxy-terminal domain of MMP12 has been shown to be a potent growth inhibitor of multiple Gram-positive and Gram-negative bacteria (12). The proenzyme form of MMP12 is secreted and subsequently activated in the phagolysosome of macrophages (12).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HOUGHTON et al [65] have shown that MMP-12 has an important role in killing of bacteria within murine macrophages; MMP-12-/-mice showed impaired bacterial clearance and increased mortality with Gram-positive and Gram-negative experimental infections. Interestingly, this effect is not mediated by the catalytic domain of the enzyme but rather by the carboxy terminal domain.…”
Section: Does Mmp-12 Participate In Human Copd?mentioning
confidence: 99%
“…Host cell proteases, such as the MΦ elastase, can exhibit bactericidal activity against Gram-positive and Gram-negative bacteria (14). To address whether FcR signaling ultimately induces activation and mobilization of host proteases to the LCV, we pretreated the host cells with cell-permeable protease inhibitors before infecting them with opsonized Lpn.…”
Section: Lpn-specific Abs Constitute the Dominant Protective Mechanismentioning
confidence: 99%